Potential biocontrol of endophytic fungi against Lasiodiplodia pseudotheobromae causal agent of cocoa dieback on cocoa seedling. Issue 2 (July 2021) - Membalik, V; Asman, A; Amin, N; Bahar, A K F
Abstract: Endophytic fungi associated with cocoa are one of the effective agents to control plant pathogens on cocoa, including the fungus Lasiodiplodia pseudotheobromae . L. pseudotheobromae cause a significant disease on cocoa, cocoa dieback. The disease is considered an emerged disease on cocoa in Sulawesi, Indonesia. The research aimed to determine the effect of the endophytic fungi on L. pseudotheobromae on cocoa seedlings. This study used a randomized block design consisting of 6 treatments and 3 replications. Five different fungi isolates were used that belong to Aspergillus genera. The treatment is three isolates of endophytes fungi (isolate T2S2LT, T245LT, T645LT), Aspergillus isolates combination, and control (with and without pathogen). The results showed that the combination of isolates and T645LT isolate was the best treatment for suppressing necrotic symptoms (leaf spot) incidence and severity. Also, T645LT isolate performed well to inhibit leaf blight symptoms incidence severity. Meanwhile, the chlorotic symptom was reduced by isolates combination, followed by T2S2LT, T645LT, and T245LT. Endophytic fungi can potentially be an important option to control cocoa dieback disease.